Validity of protein-creatinine and protein-osmolality ratios in the estimation of massive proteinuria in children with nephrotic syndrome - M. Sukmawati; K. Suarta (Indonesian Pediatric Society Publishing House, 2007)
Background Children with nephrotic syndrome have massive proteinuria, a rate of excretion equal to or greater than 40 mg/ hour/m 2 body surface. The ability to quantitate massive urinary protein excretion is very important for both diagnostic and prognostic purposes. Quantification of proteinuria using 24-hour urine collection (Esbach) is difficult to do especially in children; moreover, many false-positive and false-negative results are reported for any semi-quantitative methods such as dipstick and sulfosalicylic acid measurement. Objective To determine the accuracy of protein-creatinine ratio (PCR) and protein-osmolality ratio (POR) in quantification of massive proteinuria in children with nephrotic syndrome. Methods Diagnostic tests were conducted on children with nephrotic syndrome aged 2-12 years with Esbach as a reference standard. Sensitivity, specificity, positive predictive value (PPV), negative predictive value, (NPV), pre and posttest probability were compared between PCR and POR. Results Study patients consisted of 47 children, 38 (81%) with massive proteinuria. PCR has sensitivity of 92%, specificity of 78%, PPV of 95%, NPV of 70% and posttest probability of 95%. POR has sensitivity of 76%, specificity of 78%, PPV of 94%, NPV of 44% and posttest probability of 94%. Conclusion Both PCR and POR are accurate to determine massive proteinuria in children with nephrotic syndrome.